(untitled) (Journal of the College of Basic Education, 2023)
The problem of food production and its adequacy in Iraq, the Arab world and the world is considered one ofThe important problems that must be taken into account by countries. Because the problem is notFood production as much as there is a shortage and default in its production.Research goal:There is an interesting paradox that Iraq is mainly an agricultural country and it was expected to achieveSelf-sufficiency with regard to agricultural and animal resources, especially since it enjoys natural resourcesAnd great financial potential!!! If he suffers from a crisis in food production.As standing on this crisis and knowing its causes and immediate treatment and proposals to developfood security in the future.